Establishing Concurrent Mands for Items and Mands for Information about Location in Children with Autism - Somers, Alexis (Anal Verbal Behav, 2014)
This study replicated and extended the methodology used in Howlett et al. (Journal of Applied Behavior Analysis, 44, 943–947 2011) to bring the mands “Where’s (item)?” and “I want (item)” under appropriate antecedent control in two boys diagnosed with autism. Trials were alternated in which items were present, missing, and within view (but inaccessible) and missing and out of view. To program for generalization, fifteen items, multiple trainers, and multiple settings were used during teaching. For both participants, manding generalized to novel items, instructors, settings, and situations and maintained after 2 weeks following teaching. Results of the social validity assessment indicated that school staff found the procedures highly acceptable.